The Russian March: Investigating the Symbolic Dimension of Political Performance in Modern Russia - Zuev, D. (Europe-Asia Studies, 2013)
In this study I analyse the Russian March—a political performance which emerged in 2005 and which has developed from a protest ritual into one of the most important public and visible events organised by the Russian ultranationalist movement. The focus of the current analysis is the symbolic structure of the march, which is examined at three levels—cognitive, emotive and archetypal. The case study of the development of the Russian March highlights the paradoxes of the politics of performativity in Russia as well as the interaction between ideological codes and discursive frames in the Russian nationalist movement.